Curcumin inhibits hyperlipidemia and hepatic fat accumulation in high-fructose-fed male Wistar rats. (1st December 2016) - Maithilikarpagaselvi, Nachimuthu; Sridhar, Magadi Gopalakrishna; Swaminathan, Rathinam Palamalai; Sripradha, Ramalingam; Badhe, Bhawana
Abstract: Context: Curcumin, an active principal of Curcuma longa Linn. (Zingiberaceae), has potent antioxidant and anti-inflammatory properties. Objectives: This study investigated the effects of curcumin on hyperlipidemia and hepatic steatosis in high-fructose-fed Wistar rats. Materials and methods: Forty male Wistar rats were divided into four groups with 10 rats in each. Two groups were fed with standard rodent diet and the other two with 60% high-fructose diet for 10 weeks. Curcumin (200 mg/kg body weight) was administered along with the diets simultaneously to each of the aforementioned diet groups. After 10 weeks of experiment, blood samples were collected from tail vein. Liver, adipose and epididymal tissues were collected after sacrifice of the animals and stored for further analyses. Results: Administration of curcumin reduced body weight (280.6 ± 7.4 g), liver weight (2.5 ± 0.2 g/100 g BW), adipose weight (1.4 ± 0.3 g/100 g BW), plasma levels of TAG (86.1 ± 13.5 mg/dL), VLDL-C (17.2 ± 2.7 mg/dL), lipid ratios and increased HDL-C (28.4 ± 4.5 mg/dL) in fructose-fed rats. Curcumin supplementation significantly lowered TAG content and decreased the protein expression of LXR-α (43%) and SREBP1c (59%) in the liver. Furthermore, curcumin suppressed the expression of lipogenic enzymes, ACLY (95%), ACC (50%) and FAS (77%) in rats fed with high-fructose diet. No significant change was found in the expression of PPAR-α. Discussion and conclusion: Curcumin prevented the high-fructose induced hyperlipidemia and hepatic steatosis.